Ambient air pollution and fetal growth restriction: physician diagnosis of fetal growth restriction versus population-based small-for-gestational age - Nobles, Carrie J (Sci Total Environ, 2018)
BACKGROUND: Ambient air pollution may affect fetal growth restriction (FGR) through several mechanisms. However, prior studies of air pollution and small-for-gestational age (SGA), a common proxy for FGR, have reported inconsistent findings. OBJECTIVE: We assessed air pollution in relation to physician-diagnosed FGR and population-based SGA in the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Consecutive Pregnancy Study (2002-2010). METHODS: Among 50,005 women (112,203 singleton births), FGR was captured from medical records and ICD-9 codes, and SGA determined by population standards for birthweight <10(th), <5(th) and <3(rd) percentile. Community Multiscale Air Quality models estimated ambient levels of seven criteria pollutants for whole pregnancy, 3-months preconception, and 1(st), 2(nd) and 3(rd) trimesters. Generalized estimating equations with robust standard errors accounted for interdependency of pregnancies within participant. Models adjusted for maternal age, race/ethnicity, pre-pregnancy body mass index, smoking, alcohol, parity, insurance, marital status, asthma and temperature. RESULTS: FGR was diagnosed in 1.5% of infants, and 6.7% were <10(th), 2.7% <5(th) and 1.5% <3(rd) percentile for SGA. Positive associations of SO(2), NO(2) and PM(10) and negative associations of O(3) with FGR were observed throughout preconception and pregnancy. For example, an interquartile increase in whole pregnancy SO(2) was associated with 16% (95% CI 8%, 25%) increased FGR risk, 17% for NO(2) (95% CI 9%, 26%) and 12% for PM(10) (95% CI 6%, 19%). Associations with SGA were less clear. CONCLUSIONS: Chronic exposure to air pollution may be associated with FGR but not SGA in this low-risk population.